Three new species of the ghost moth Magnificus Yan from China and India (Lepidoptera, Hepialidae) - Grehan, John R.; Saldaitis, Aidas; Prozorov, Alexey M.; Yakovlev, Roman V.; Müller, Günter C.; Ignatev, Nikolai; Mielke, Carlos G. C.; Xu, Zhen-Bang; Duan, Yang; Dūda, Juozas (Zootaxa, 2025)
Three new species of Magnificus Yan, 2000 are described: M. florianii sp. nov. from western Yunnan and M. shaosiming sp. nov. from southern Shaanxi, both in China, and M. ignatevi sp. nov. from West Bengal, India. Six female specimens that could not be positively attributed to any of the species described in this paper were investigated; five specimens (morphotype 1) are considered most similar to Magnificus bouvieri (Oberthür, 1913), and one (morphotype 2) to Magnificus dirschi (Bang-Haas, 1939). These two determinations are described here in detail for future evaluation of the genus. The current southern distributional boundary seems to correspond to two tectonic boundaries—the subduction zone between India and Asia, and the Red River Fault, marking a major tectonic boundary resulting from the accretion of the Indian continent. These tectonic boundaries are consistent with the Laurasian ancestral range, but the new Himalaya record is an indication that Magnificus may be more widely distributed in eastern Asia.